Do Market Performance of SOEs Outperform Private Firms? (A Case of Indonesia Exchange) - Nur Khamisah; Anisa Listya; Ruth Samantha Hamzah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The purpose of the privatization strategy is to improve the performance of Stated Owned Enterprises (SOEs) that are considered to have a poor performance that is not better than the private companies. The data is collected from the company's annual report and from the Osiris Database. This research uses purposive sampling method and doing multiple linear regression test analysis to test the research hypothesis. The final sample in this study consisted of 454 company observation. This study finds that privatized SOEs have better levels of market performance than private companies. Regression test results show the coefficient of market performance of SOEs is positive and significant at the level 1%. These results indirectly indicate that the privatization strategy through IPO conducted by the government against several SOEs has been effective in improving the performance of BUMNs